A novel integrated pyrolysis-gasification technology for improving quality of bio-gases from multisource solid wastes. Issue 1 (December 2020) - Li, Aishu; Hu, Song; Han, Hengda; Huang, Haizhou; Guo, Tingting; Xiang, Jun; Wang, Yi
Abstract: Recovery and utilization of municipal solid waste (MSW) into syngas has already attracted the attention of researchers for years. However, until now the MSW such as sewage sludge and plastics still lack a way of industrial utilization due to the relatively low transformation efficiency or low gas quality. Accordingly, a novel integrated pyrolysis-gasification technology is proposed in this study, in which the volatiles and steam released from the pyrolysis of sewage sludge at 450°C take part in the gasification of plastic at 600 °C-800°C, taking advantage of high-water content of sludge to produce high quality bio-gas. At the same time, the synergistic effect between sludge pyrolysis and plastic gasification was explored by product analysis. Compared to pyrolysis or gasification alone, the aromatic degree of the bio-oil obtained by the integrated technology under pyrolysis at 450°C and gasification at 700°C weakens. Whereas, the aromatic degree of the bio-oil obtained at 450°C (pyrolysis) and 800°C (gasification) deepens, and the yield of C2 Hy in the bio-gas improves markedly. The higher temperature promotes the decomposition and condensation of macromolecules and also strengthens the influence of volatiles and steam from sludge pyrolysis on the structural fracture of plastics during gasification to some extent. In conclusion, this technology can significantly improve bio-gas yield and quality at high temperature.